Kinetics and incidence of anti-natalizumab antibodies in multiple sclerosis patients on treatment for 18 months. - Oliver-Martos, Begoña; Fernández, Óscar; Orpez, Teresa; Alvarenga, Marco Papais; Pinto-Medel, María Jesús; Guerrero, Miguel; León, Antonio; López-Madrona, José Carlos; Maldonado-Sánchez, Rafael; García-León, Juan Antonio; Luque, Gloria; Fernández, Victoria; et al. (SAGE, 2011)
Natalizumab is a monoclonal antibody shown to be highly effective in the treatment of relapsing-remitting multiple sclerosis (RRMS). Patients treated with natalizumab can develop antibodies directed against this agent that may affect the efficacy and safety of the drug. In this observational study, the kinetics of the appearance and the incidence of anti-natalizumab antibodies were followed prospectively for 18 months in a cohort of 64 consecutive patients treated with natalizumab for relapsing MS. Blood samples were drawn immediately before starting natalizumab therapy and each month afterwards. The presence of antibodies against natalizumab was assessed by enzyme-linked immunosorbent assay (ELISA) in all patients. Anti-natalizumab antibodies were detected in nine (14.1%) natalizumab-treated patients, three (4.68%) of whom were transiently positive while six (9.37%) were persistently positive (these patients discontinued natalizumab). All positive titres were observed during the first 4 months of treatment. One patient with a hypersensitivity reaction also had persistent antibodies. We conclude that antibodies against natalizumab develop early, within the first 6 months of therapy with natalizumab. Although no antibodies were detected after 4 months of therapy in this particular study, this does not rule out their development later on in exceptional cases.
Keywords: Esclerosis múltiple; multiple sclerosis